Salt pumping by voltage-gated nanochannels - Tagliazucchi, Mario Eugenio (2015)
This Letter investigates voltage-gated nanochannels, where both the potential applied to the conductive membrane containing the channel (membrane potential) and the potential difference between the solutions at both sides of the membrane (transmembrane potential) are independently controlled. The predicted conductance characteristics of these fixed-potential channels dramatically differ from those of the widely studied fixed-charge nanochannels, in which the membrane is insulating and has a fixed surface charge density. The difference arises because the transmembrane potential induces an inhomogeneous charge distribution on the surface of fixed-potential nanochannels. This behavior, related to bipolar electrochemistry, has some interesting and unexpected consequences for ion transport. For example, continuously oscillating the transmembrane potential, while holding the membrane potential at the potential for which it has zero charge in equilibrium, creates fluxes of neutral salt (fluxes of anions and cations in the same direction and number) through the channel, which is an interesting phenomenon for desalination applications.